Raw material studies of West Central Serbia - Vera Bogosavljević Petrović; Jelena Marković (Journal of Lithic Studies, 2014)
This paper deals with raw material problems in the territory of West Central Serbia geologically determined as the Čačak-Kraljevo (or West Morava) basin. Our research is presented through the most striking case studies, Lojanik, Vlaška Glava and Lazac. The Lojanik hill is a silicified forest by origin. It has occasionally been in use from the earliest periods of prehistory until today as a source of black and ochre-coloured flint, opal and silicified wood. A detailed prospection, including the mapping of surface finds using square nets, was conducted during two research campaigns. The Vlaška Glava is an open-air Palaeolithic site at which artefacts made of white, ochre, red, brown and black chert, silicified magnesite, volcanic and metamorphic rocks were found. Our research of primary and secondary geological deposits in the vicinity of the site showed equivalent raw material. We also found an interesting primary deposit of high quality bluish grey flint with outcrop activities (Workshop 1). The Lazac shaft is a contemporary magnesite mine, recently abandoned because of the high percentage of silicon-dioxide. We determined the same raw material in collections found at nearby Neolithic sites. Certain similarities between the wooden support systems of ore exploration in the Middle Ages and modern times were established at the entrance of the shaft. Our research in the territory of the West Morava basin resulted in reconstruction of some links between geological deposits and settlements and also creation of a relevant base for future raw material studies.